THE INFLUENCE OF LEARNING MOTIVATION, LEARNING ENVIRONMENT, AND LEARNING DISCIPLINE ON LEARNING ACHIEVEMENT OF BANDAR LAMPUNG UNIVERSITY MANAGEMENT STUDENTS - Lestari, Bebi Prima; Alam, Iskandar Ali (Transpublika Publisher, 2024)
In carrying out this research, the aim is to find out how learning motivation, learning environment, and learning discipline influence the learning achievements of students studying management at Bandar Lampung University. This research sample involved 87 students majoring in management at Bandar Lampung University, which represents the population used as research subjects. In carrying out this research, we utilized a technique in the form of multiple linear regression analysis. In carrying out data collection using the questionnaire method, and after processing the t-test results revealed a number of findings: (1) That learning achievement is significantly influenced by learning motivation (2) Learning achievement is not significant and is not influenced by the learning environment (3) Learning achievement is also significantly influenced by learning discipline (4) Based on the F test, it states that learning achievement in conclusion gets its influence from the variables of learning motivation, learning environment, and learning discipline with a significant value of 0.000 <0.05.